Demark’s method supporting for forecasting of vectors internal and temporary numbers - Klimenko, I. V. (Science and Transport Progress, 2011)
In the article the use of method of T. Demark for construction of the operative forecast of the basic indicators of activity of railway transport enterprises is offered.